Intraabdominal Chemotherapy of Prevailing Forms of Colon Cancer - A. P. Zhuchenko; I. D. Kalganov; A. F. Filon (Антибиотики и Химиотерапия)
The efficacy of intraabdomlnal chemotherapy in patients with prevailing forms of colon cancer, such as peritoneal carcinomatosis, local disseminated and local recurrent colon cancer was estimated. The comparative analysis showed that the intraabdominal chemotherapy allowed to amend the remote results of the treatment in the cases with carcinomatosis, local disseminated colon cancer and local recurrence.